Analisis Daya Saing Ekspor Feronikel Indonesia dan Determinan yang Mempengaruhi Volume Ekspor di Empat Negara Tujuan Tahun 2006-2022 - Khairunisa, Addina; Ervani, Eva (PPJP ULM, 2024)
This research aims to analyze the competitiveness of Indonesian ferronickel in the four destination countries with the most transactions, and analyze the factors that influence the volume of Indonesian ferronickel exports, using a gravity model. The data used in this research is panel data from four countries from 2006-2022, using the Revealed Comparative Advantage (RCA) and Poisson Pseudo Maximum Likelihood (PPML) methods. The results show that the RCA value in the four countries is greater than 1, meaning that Indonesian ferronickel has competitiveness in the destination country. Then, the factors that significantly influence the volume of Indonesian ferronickel exports are Indonesia's GDP, the GDP of the destination country, the exchange rate, and the COVID-19 pandemic with a positive coefficient, as well as the population of the destination country with a negative coefficient. Meanwhile, the economic distance variable doesn’t have a significant effect on the volume of Indonesian ferronickel exports.